Use of Music Therapy as an Audiological Rehabilitation Tool in the Elderly Population: A Mini-Review - Grenier, Anne Sophie; Lafontaine, Louise; Sharp, Andréanne (Frontiers in Neuroscience, 2021)
It is well known and documented that sensory perception decreases with age. In the elderly population, hearing loss and reduced vestibular function are amongst the most prevalent affected senses. Two important side effects of sensory deprivation are cognitive decline and decrease in social participation. Considering that hearing loss, vestibular function impairment, cognitive decline all lead to decrease in social participation. Altogether, these problems have a great impact on the quality of life of the elderly. This is why a rehabilitation program covering all of these aspects would therefore be useful for clinicians. It is well-known that long-term music training can lead to cortical plasticity. Behavioral improvements have been measured for cognitive abilities and sensory modalities (auditory, motor, tactile, visual) in healthy young adults. Based on these findings, it is possible to wonder if this kind of multisensory training would be an interesting therapy to improve not only communication, but also help with posture and balance, cognitive abilities and social participation. The aim of this review is to assess and validate the impact of music therapy in the context of hearing rehabilitation in older adults. Musical therapy seems to have a positive impact on auditory perception, posture and balance, social integration and cognition. While the benefits seem obvious, the evidence in the literature is scarce. However, there is no reason not to recommend the use of music therapy as an adjunct to audiological rehabilitation in the elderly when possible. Further investigations are needed to conclude on the extent of the benefits that music therapy could bring to older adults. More data is needed to confirm which hearing abilities can be improved based on the many characteristics of hearing loss. There is also a need to provide a clear protocol for clinicians on how this therapy should be administered to offer the greatest possible benefits.